Managing radioactively contaminated land: a method to assist the design of long-term remediation strategies - Cox, Glen Michael (2004)
This thesis describes the development of a system to assist the design of long-term remediation strategies for radioactively contaminated land. Existing radiological models, that estimate the uptake of radionuclides by plants and the doses arising from exposure to external radiation, were combined with a spatially implemented food-chain model, to allow the temporal and spatial variation of radionuclide transport through the terrestrial environment, and the resulting doses of exposed human populations, to be estimated. Doses are estimated using a novel method for the simulation of human populations, which includes the generation of sub-populations by Monte-Carlo sampling and consideration of the geographical origins of consumed food products. Various simulated radiological countermeasures have been incorporated into the system (e.g. clean-feeding of livestock), allowing the effects of potential remediation strategies to be assessed. Furthermore, a method has been developed which efficiently identifies the optimum set of countermeasures for a given scenario according to a defined merit function using cost benefit analysis, which can be extended to include terms that account for the preference for averting high levels of individual dose, and the social costs of a number of countermeasure side-effects (e.g. disruption of normal daily life).